HeaTherm / Mohd Ghazali Mujiyo - Mujiyo, Mohd Ghazali (2020)
Our company, Creative Electronic Sdn Bhd is actually a local company, specializing and participating in delivering a new approach of technology for the consumers to have. The product and the company itself was established, to deliver a ‘green’ products which adopts the principle of sustainability at which we try to offer an alternative of technology. This kind of technology will allow the consumers to continue living their digital lives, but with lesser digital footprints or negative impacts towards the environment. Founders, who mostly come from background related environmental sciences see the needs for them to act, not to just inducing cash inflows but also for the sake of the Mother Nature. Moreover, our product will mainly target working people, party goers, and youngster as they are the main consumers in this industry. We will be selling our product in the state of Johor Bharu at RM99.00. This is price is quite reasonable and affordable as compared to our competitors. Due to good competitive advantages, aided by the trends in the markets, profits are forecasted to be around RM 99 thousands within the very first term of business venture. This value seems good enough for a new company like us, where we can further develop and improve our products, with the gained profits.